Photoprotection according to skin phototype and dermatoses: practical recommendations from an expert panel. (4th May 2021) - Passeron, T.; Lim, H.W.; Goh, C.‐L.; Kang, H.Y.; Ly, F.; Morita, A.; Ocampo Candiani, J.; Puig, S.; Schalka, S.; Wei, L.; Dréno, B.; Krutmann, J.
Abstract: Increasing evidence on the impact of the different wavelengths of sunlight on the skin demonstrates the need for tailored recommendations of sunscreen according to skin phototype and dermatoses, which is now possible due to advances in the filters and formulations of sunscreens. A selective literature search was performed by an international expert panel, focusing on the type of sunscreen to recommend for photoaging, skin cancers, photodermatoses, pigmentary disorders and skin inflammatory disorders. Protection against ultraviolet (UV)B is especially important for light skin as there is a high risk of sunburn, DNA damage and skin cancers. Darker skin may be naturally better protected against UVB but is more prone to hyperpigmentation induced by visible light (VL) and UVA. Protection against UVA, VL and infrared A can be helpful for all skin phototypes as they penetrate deeply and cause photoaging. Long‐wave UVA1 plays a critical role in pigmentation, photoaging, skin cancer, DNA damage and photodermatoses. Adapting the formulation and texture of the sunscreen to the type of skin and dermatoses is also essential. Practical recommendations on the type of sunscreen to prescribe are provided to support the clinician in daily practice.